Quality comparison of vinegar with traditional semi-solid natural fermentation and submerged fermentation from Zhejiang - ZHANG Fei, CHANG Guoli, LU Donghao, XU Weijiang, JIANG Yipeng, ZHU Junli, WANG Xinyu, LIU Xueying, LU Haixia (Zhongguo niangzao)
In order to compare the quality of Zhejiang traditional semi-solid naturally fermented vinegar (M1 and M3) and submerged fermented vinegar (M2 and M4), the physicochemical properties, active components, volatile flavor compounds, and antioxidant activities of M1-M4 were measured, sensory properties were evaluated, and the correlation analysis based on the results was conducted. The results showed that the contents of reducing sugar, amino acid nitrogen, total phenols, and total flavonoids in M1 and M3 were significantly higher than those in M2 and M4 (P<0.05), a total of 8 organic acids and 17 free amino acids (including 8 essential amino acids) were identified in M1-M4, the contents of sweet and bitter amino acids in M1 and M3 were significantly higher than those in M2 and M4 (P<0.05), while the acetic acid contents in M2 and M4 (5.64 g/100 ml, 6.43 g/100 ml) were significantly higher than those in M1 and M3 (3.87 g/100 ml, 3.42 g/100 ml) (P<0.05). Compared to submerged fermented vinegar, traditional semi-solid naturally fermented vinegar had stronger antioxidant activity and better sensory quality. A total of 112 volatile flavor compounds were identified in M1-M4, and the total contents of volatile flavor compounds in the 4 vinegar samples were M4 (801.21 mg/L)>M3 (615.16 mg/L)>M1 (562.37 mg/L)>M2 (241.03 mg/L). Correlation analysis results showed that acetone and 3-acetyl-2-butanone could improve the ester aroma and sweetness, while amino acid nitrogen showed a significant positive correlation with sweetness (P<0.05). In conclusion, traditional semi-solid naturally fermented vinegar was superior in quality and sensory properties.